Comparison of molar intrusion efficiency and bone density by CT in patients with different vertical facial morphology. (16th December 2014) - Ding, W.H.; Li, W.; Chen, F.; Zhang, J. F; Lv, Y.; Chen, X.Y.; Lin, W.W.; Fu, Z.; Shi, J.J.
Summary The purpose of this study is to examine the relationship between molar intrusion efficiency and bone density in patients with different vertical facial morphology. Thirty‐six female patients, with overerupted upper first molars, were divided into two groups according to mandiblular plane angle (FH‐MP): hyperdivergent, FH‐MP>30° (G1), hypodivergent, FH‐MP<22° (G2). Mini‐screw implants with elastic chains were used to intrude upper first molars. Spiral CT was used to measure the intrusion degree of upper first molar and bone density, and molar intrusion efficiency was calculated as amount/duration (mm month−1). In addition, each tooth was divided into three portions (cervical, furcation and apical) to measure the bone density. It was found in this study that treatment duration was 3·13 and 4·71 months in G1 and G2 and that the intrusion efficiency was 1·57 and 0·81 in G1 and G2 with significant difference (P < 0·05). There were significant differences in cervical, furcation and apical bone density between two groups (P < 0·05). The bone density was significantly reduced after molar intrusion. In addition, the bone density change was greater in G1 than in G2 (P < 0·05). It was concluded that molars were more easily to be intruded in hyperdivergent than in hypodivergent patients. The difference of bone density and bone density changes during intrusion may account for the variation of molar intrusion efficiency.